1991
DOI: 10.1021/j100154a044
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of the photocatalytic behavior of titania: particles in a photoelectrochemical slurry cell and the relevance to photodetoxification reactions

Abstract: A mechanism is developed that describes the transient photoelectrochemical response of Ti02 particles in a photoelectrochemical slurry cell. The specific effects of addition of reductants and oxidants are consistent with the proposed mechanism. The relevance of the proposed mechanism to the use of TiO: particles for water photodetoxification is examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(82 citation statements)
references
References 1 publication
3
79
0
Order By: Relevance
“…The degradation of formic acid is reported to proceed both via indirect (the hydroxyl route) (Kesselman, Weres, Lewis, & Ho mann, 1997;Peterson, Turner, & Nozik, 1991) and via direct attack (uptake of h + ) (Bideau, Claudel, & Otterbein, 1980;Pelizzetti & Minero, 1993;Prairie, Evans, Stange, & Martinez, 1993;Upadhya & Ollis, 1997), presented in Table 1 as reaction (R8) and (R9), respectively. Following the measurements of Kesselman et al (1997), the indirect route is taken as the dominant reaction route.…”
Section: Modelmentioning
confidence: 99%
“…The degradation of formic acid is reported to proceed both via indirect (the hydroxyl route) (Kesselman, Weres, Lewis, & Ho mann, 1997;Peterson, Turner, & Nozik, 1991) and via direct attack (uptake of h + ) (Bideau, Claudel, & Otterbein, 1980;Pelizzetti & Minero, 1993;Prairie, Evans, Stange, & Martinez, 1993;Upadhya & Ollis, 1997), presented in Table 1 as reaction (R8) and (R9), respectively. Following the measurements of Kesselman et al (1997), the indirect route is taken as the dominant reaction route.…”
Section: Modelmentioning
confidence: 99%
“…Two kinds of dependence had been suggested: the kinetic constant can be a function of the square root of the radiation entering at high light intensities (Bahnemann et al, 1991) or a linear function of the radiation entering at low light intensities (Peterson et al, 1991). In fact, it is better to use the exponential dependence to express the relationship between the first-order kinetic constant and the light intensity.…”
Section: The Pec Oxidation Rate Affected By Addition Of Sodium Peroxomentioning
confidence: 99%
“…Square-root intensity dependence was observed with rutile I, rutile 11, anatase, uncoated anatase pigment and platinized anatase and also independent on wavelength of incident radiation Hussein & Rudham, 1987). Bahnemann et al, (1991) reported that the change in kinetic constant is a function of the square root of the radiation entering at high light intensities, while this change can be linear with light intensity of incident radiation low light intensities (Peterson et al, 1991). Ollis et al, (1991) summarize the effect of light intensity on the kinetics of the photocatalytic degradation of dye as follows: a.…”
Section: Effect Of Light Intensitymentioning
confidence: 99%